Effects of compositions on properties of PEO-KI-I-2 salts polymer electrolytes for DSSC - Kalaignan, GP; Kang, MS; Kang, YS (ELSEVIER SCIENCE BV, 2006)
The effects of compositions on properties of PEO/KI/I-2, salts polymer electrolytes were investigated to optimize the photovoltaic performance of solid state DSSCs. XRD pattern for the mole ratio 12:1 of [EO:KI] was showed the formation of complete amorphous complex. DSC results also confirmed the amorphous nature of the polymer electrolyte. The highest value of ionic conductivity is 8.36 x 10(-5) S/cm at 303 K (ambient temperature) and 2.32 x 10(-4) S/cm at 333 K (moderate temperature) for the mole ratio 12:1 of EO:KI complex. The effect of contribution of [I-] and [I-3(-)] concentration with conductivity were also evaluated. FTIR spectrum reveals that the alkali metal cations were co-ordinated to ether oxygen of PEO. The formation of polyiodide ions, such as symmetric I-3(-) (114 cm(-1)) and I-5(-) (145 cm(-1)) caused by the addition of iodine was confirmed by FT Raman spectroscopic measurements. The optimum composition of PEO-KI-I-2 polymer electrolyte system for higher conductivity at ambient and moderate temperatures was reported. A linear Arrhenius type behaviour was observed for all the PEO-KI polymer complexes. Transport number measurements were carried out for several polymer electrolyte compositions. Dye-sensitized solar cells were fabricated by using higher conductivity polymer electrolyte compositions and its photoelectrochemical performance was investigated. The fill factor, short-circuit current, photovoltage and energy conversion efficiency of the DSSC assembled with optimized electrolyte composition were calculated to be 0.563, 6.124 mA/cm(2), 593 mV and 2.044% respectively. (c) 2006 Elsevier B.V. All fights reserved.
Keywords: NANOCRYSTALLINE SOLAR-CELLS; SENSITIZED PHOTOELECTROCHEMICAL CELL; SOLID-STATE; POLY(ETHYLENE OXIDE); CHARGE-TRANSFER; TRIIODIDE ION; CONDUCTIVITY; TRANSPORT; RAMAN; FILM